Biblia Ekumeniczna w języku polskim na tle wybranych ekumenicznych projektów przekładowych Pisma Świętego - Wojtyra, Krzysztof Jan (The Biblical Annals, 2023)
The author shows the peculiarities of the ecumenical translation of the Bible into Polish against the background of the most important ecumenical translation projects into other languages. The aim of the research was to present the features of Polish inter-confessional translation. The author presented the history of earlier inter-Christian translations of the Bible into Polish, the team-committee method in the work on the translation of the Bible and its impact on ecumenism and the achieved effect. The research followed a historical method based on use of introductions to ecumenical Bibles in foreign languages and on never published archives from the Bible Society in Poland. Another group of sources are recension and papers on the ecumenical Bible. The results of the studies carried out similarities and differences between the foreign ecumenical translations and the Polish edition; the specificity of the polish biblical style of the ecumenical Bible; the reasons for such a late appearance of the Polish ecumenical Bible.